Effect of pulmonary hypertension on outcome of pulmonary tuberculosis. (March 2015) - Marjani, Majid; Tabarsi, Payam; Baghaei, Parvaneh; Moniri, Afshin; Malekmohammad, Majid
Abstract: Objectives: Pulmonary hypertension is a serious disorder with catastrophic outcomes. This study aimed to evaluate the effect of pulmonary arterial hypertension on the outcome among new cases of pulmonary tuberculosis. Novel modalities are available as therapeutic options, so early diagnosis of pulmonary arterial hypertension may be important. Methods: In a cross-sectional study, 777 new cases of pulmonary tuberculosis were recruited in the National Research Institute of Tuberculosis and Lung Disease, Tehran, Iran. Pulmonary arterial pressure was measured by resting transthoracic echocardiography on the beginning of tuberculosis treatment. Echocardiography was performed by a cardiologist expert in the field. Patients with systolic pulmonary arterial pressure more than 35 mmHg were defined as pulmonary hypertensive. The relationship between pulmonary arterial hypertension and mortality was assessed during six months of tuberculosis treatment. Results: Seventy-four (9.5%) of 777 new cases of pulmonary tuberculosis had pulmonary arterial hypertension. Among them, 10 (13.5%) died during the treatment period. In comparison with 5% mortality among cases without pulmonary arterial hypertension, death was significantly associated with pulmonary hypertension ( P  = 0.007). Logistic regression analysis showed that pulmonary arterial pressure more than 35 mmHg is an independent predictor of death among tuberculosis patients. Conclusion: Among new cases of pulmonary tuberculosis, a significant association between mortality and pulmonary arterial pressure >35 mmHg was found. Therapeutic intervention may change the outcome of these patients.